Far-red pentamethine cyanine dyes as fluorescent probes for the detection of serum albumins - D. Aristova; G. Volynets; S. Chernii; M. Losytskyy; A. Balanda; Yu. Slominskii; A. Mokhir; S. Yarmoluk; V. Kovalska (Royal Society Open Science, 2020)
Benzothiazole based cyanine dyes with bridged groups in the pentamethine chain were studied as potential far-red fluorescent probes for protein detection. Spectral-luminescent properties were characterized for unbound dyes and in the presence of serum albumins (bovine (BSA), human (HSA), equine (ESA)), and globular proteins (β-lactoglobulin, ovalbumin). We have observed that the addition of albumins leads to a significant increase in dyes fluorescence intensity. However, the fluorescent response of dyes in the presence of other globular proteins was notably lower. The value of fluorescence quantum yield for dye bearing a sulfonate group complexed with HSA amounted to 42% compared with 0.2% for the free dye. The detection limit of HSA by this dye was greater than 0.004 mg ml−1 which indicates the high sensitivity of dye to low HSA concentrations. Modelling of structure of the dyes complexes with albumin molecules was performed by molecular docking. According to these data, dyes could bind to up to five sites on the HSA molecule; the most preferable are the haemin-binding site in subdomain IB and the dye-binding site in the pocket between subdomains IA, IIA and IIIA. This work confirms that pentamethine cyanine dyes could be proposed as powerful far-red fluorescent probes applicable for highly sensitive detection of albumins.